CXCR4-BTK axis mediate pyroptosis and lipid peroxidation in early brain injury after subarachnoid hemorrhage via NLRP3 inflammasome and NF-κB pathway - Chengli Liu; Kun Yao; Qi Tian; Yujia Guo; Guijun Wang; Peibang He; Jianfeng Wang; Jian Wang; Zhan Zhang; Mingchang Li (Redox Biology, 2023)
C-X-C chemokine receptor type 4 (CXCR4) is critical for homeostasis of the adaptive and innate immune system in some CNS diseases. Bruton's tyrosine kinase (BTK) is an essential kinase that regulates inflammation in immune cells through multiple signaling pathways. This study aims to explore the effect of CXCR4 and BTK on neuroinflammation in the pathogenesis of early brain injury (EBI) after subarachnoid hemorrhage (SAH). Our results showed that the expression of CXCR4 and p-BTK increased significantly at 24 h after SAH in vivo and in vitro. Ibrutinib improved neurological impairment, BBB disruption, cerebral edema, lipid peroxidation, neuroinflammation and neuronal death at 24 h after SAH. Inhibition of BTK phosphorylation promoted the in vitro transition of hemin-treated proinflammatory microglia to the anti-inflammatory state, inhibited the p-P65 expression and microglial pyroptosis. NLRP3 deficiency can significantly reduce pyroptosis in SAH mice. Moreover, CXCR4 inhibition can suppress NLRP3-mediated pyroptosis, NF-κB activation and NOX2 expression in vitro, and ibrutinib can abolish CXCR4-aggravated BBB damage and pyroptosis in EBI after SAH. The levels of CXCR4 in CSF of SAH patients is significantly increased, and it is positively correlated with GSDMD and IL-1β levels, and have a moderate diagnostic value for outcome at 6-month follow-up. Our findings revealed the effect of CXCR4 and P-BTK on NLRP3-mediated pyroptosis and lipid peroxidation after SAH in vivo and in vitro, and the potential diagnostic role of CXCR4 in CSF of SAH patients. Inhibition of CXCR4-BTK axis can significantly attenuate NLRP3-mediated pyroptosis and lipid peroxidation by regulating NF-κB activation in EBI after SAH.